Maeckes logo

<    1      2      3      4      5      6      7      8      9     10    >


Antilogarithm

In an exponential function the exponent can be a logarithm

e ln x = x

 


Explanation

We take the exponential function

e n = x

and want to calculate n. So we must answer the question: To what power do I need to raise the base e to get x ? The answer is

to the power   ln x

The spelling scares everyone off in the beginning. Let's just remember that a logarithm is the inverse of an exponential function.

 


Example 1

From the definition of the logarithm follows that you can write each number as a power, so

1 = eln (1)

And because ln (1) = 0 you get

1 = eln (1) = e0 = 1

The zeroth power always delivers the value 1.

 


Deutsch   Español   Français   Nederlands